Early warning systems for more effective student counselling in higher education: Evidence from a Dutch field experiment. (9th February 2021) - Plak, Simone; Cornelisz, Ilja; Meeter, Martijn; van Klaveren, Chris
Abstract: Early Warning Systems (EWS) in higher education accommodate student counsellors by identifying at‐risk students and allow them to intervene in a timely manner to prevent student dropout. This study evaluates an EWS that shares student‐specific risk information with student counsellors, which was implemented at a large Dutch university. A randomised field experiment was conducted to estimate the effect of EWS‐assisted counselling on first‐year student dropout and academic performance. The results show that the EWS accurately predicts at‐risk students. Yet, EWS‐assisted counselling did not reduce dropout, nor improved academic performance. Solving the underlying problem of poor academic performance might require additional actionable feedback and recommended counselling practices. Samenvatting: Early Warning Systems (EWS) ondersteunen studieadviseurs in het hoger onderwijs door studenten in nood te signaleren en zo vroegtijdige interventies mogelijk te maken om studentuitval te voorkomen. Deze studie evalueert de implementatie van een EWS die student‐specifieke risico‐informatie deelde met studieadviseurs op een grote Nederlandse universiteit. Om het effect van EWS‐ondersteund advies op eerstejaarsuitval en prestaties te schatten werd een gerandomiseerd veldexperiment uitgevoerd. De resultaten tonen dat het EWS accuraat studenten in nood signaleert. Echter, verminderde EWS‐ondersteund advies studentuitval niet, en waren prestaties ook niet verbeterd. De oplossing voor het onderliggende probleem van onvoldoende academische prestaties ligt wellicht in het aanbieden van aanvullende praktische feedback en aanbevolen begeleidingsprocedures.